-
Notifications
You must be signed in to change notification settings - Fork 1
/
Copy pathPOLY2008.tex
133 lines (93 loc) · 6.17 KB
/
POLY2008.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
-------------------------------------------------------------------------------
\begin{problem}[Posted by \href{https://artofproblemsolving.com/community/user/29721}{Erken}]
Find all $ n\in\mathbb{N}$ such that polynomial
\[ P(x) = (x - 1)(x - 2) \cdots (x -n)\]
can be represented as $Q(R(x))$, for some polynomials $ Q(x)$ and $R(x)$ with degree greater than $1$.
\flushright \href{https://artofproblemsolving.com/community/c6h183353}{(Link to AoPS)}
\end{problem}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/29428}{pco}]
\begin{tcolorbox}Find all $ n\in\mathbb{N}$,such that polynomial
$ P(x) = (x - 1)(x - 2)\dots (x - n)$
can be represented as $ Q(R(x))$,for some non-constant polynomials $ Q(x),R(x)$.\end{tcolorbox}
It seems I misunderstood something because this problem seems trivial :
Any non constant polynomial $ P(x)$ can be represented as $ Q(R(x))$,for some non-constant polynomials $ Q(x),R(x)$ :
Take $ R(x)=x+a$ and $ Q(x)=P(x-a)$
\end{solution}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/29721}{Erken}]
\begin{tcolorbox}[quote="Erken"]Find all $ n\in\mathbb{N}$,such that polynomial
$ P(x) = (x - 1)(x - 2)\dots (x - n)$
can be represented as $ Q(R(x))$,for some non-constant polynomials $ Q(x),R(x)$.\end{tcolorbox}
It seems I misunderstood something because this problem seems trivial :
Any non constant polynomial $ P(x)$ can be represented as $ Q(R(x))$,for some non-constant polynomials $ Q(x),R(x)$ :
Take $ R(x) = x + a$ and $ Q(x) = P(x - a)$\end{tcolorbox}
Sorry,i forgot to write,that
$ deg(R),deg(Q)\geq 2$.
\end{solution}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/29721}{Erken}]
[hide="hint"]
Consider two cases,when $ n$ is odd,and when it is an even number
[\/hide]
\end{solution}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/25787}{olorin}]
If $ n > 2$ is even, then
$ P(x) = \prod_{k = 1}^{n\/2}(x - k)(x - (n + 1 - k)) \\
\hspace*{0.3in} = \prod_{k = 1}^{n\/2}((x - 1)(x - n) + k(n + 1 - k) - n) = Q(R(x))$
with $ R(x) = a(x - 1)(x - n) + b\in\mathbb{R}[x]$ non-linear
and $ Q(x) = \prod_{k = 1}^{n\/2}\left({x - b\over a} + k(n + 1 - k) - n\right)\in\mathbb{R}[x]$ non-linear
for any $ a,b\in\mathbb{R},a\not = 0$.
I'll show, that these are the only $ Q(x),R(x)\in\mathbb{R}[x]$ non-linear with $ P(x) = Q(R(x))$.
Say $ q: = \deg Q\ge 2$ and $ r: = \deg R\ge 2$. Then $ n = qr$.
We can replace $ R(x)$ with $ {1\over a}R(x)$ and $ Q(x)$ with $ Q(ax)$ for any $ a\in\mathbb{R},a\not = 0$.
Similar we can replace $ R(x)$ with $ R(x) - R(1)$ and $ Q(x)$ with $ Q(x + R(1))$.
So we can assume $ R(x)$ has leading coefficient $ 1$ and $ R(1) = 0$.
From [url=http://www.mathlinks.ro/Forum/viewtopic.php?p=733142&search_id=2134256501#733142]here[\/url] we see, that the strictly monotonic sequences
$ R(1 + kq),R(2 + kq),\ldots,R((k + 1)q)$ and
$ R(1 + (k + 1)q),R(2 + (k + 1)q),\ldots,R((k + 2)q)$
run through all the roots of $ Q(x)$ in converse order for all $ k = 0,1,\ldots ,r - 2$.
This gives
$ (*)$ $ R(k) = R(2q + 1 - k)$ for all $ k = 1,2,\ldots 2q$.
and
$ (**)$ $ R(k) = R(k + 2q)$ for all $ k = 1,\ldots ,n - 2q$.
For $ r\ge 3$ and $ (q,r)\not = (2,3)$ we have $ 1 < (q - 1)(r - 2)$ and $ r - 1 < qr - 2q = n - 2q$.
Then by $ (**)$ $ R(x) - R(x + 2q)$ has $ n - 2q$ different roots and degree $ \le\deg R - 1 < n - 2q$.
So $ R(x) = R(x + 2q)$ and $ R(1) = 0$ gives infinitely many roots $ 1 + 2qk$ of $ R(x)$ for $ k\in\mathbb{N}$,
and therefore $ R(x)\equiv 0$. Contradiction!
For $ (q,r) = (2,3)$ we get $ 0 = R(1) = R(4) = R(5)$ using $ (*)$ and $ (**)$.
This gives $ R(x) = (x - 1)(x - 4)(x - 5)$ and $ R(2) = 6,R(3) = 4$, which contradicts $ (*)$.
So $ r = 2$ and $ n = 2q > 2$ even and $ (*)$ gives $ 0 = R(1) = R(n)$.
Then $ R(x) = (x - 1)(x - n)$ and $ P(x) = Q(R(x)) = \tilde{Q}(R(x))$
with $ \tilde{Q}(x) = \prod_{k = 1}^{n\/2}(x + k(n + 1 - k) - n)\in\mathbb{R}[x]$.
This gives $ Q(x) = \tilde{Q}(x)$, which completes the proof.
($ Q(x) - \tilde{Q}(x)$ has infinitely many roots $ x=R(y),y\in\mathbb{R}$)
\end{solution}
*******************************************************************************
-------------------------------------------------------------------------------
\begin{problem}[Posted by \href{https://artofproblemsolving.com/community/user/25101}{radio}]
Find all polynomials $ P(x)\in \mathbb R[x]$ such that
$$ P(x^2)=P(x)P(x+2),$$
for all $x\in \mathbb R$.
\flushright \href{https://artofproblemsolving.com/community/c6h184257}{(Link to AoPS)}
\end{problem}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/32247}{Jure the frEEEk}]
let $ a$ be a complex root of $ P$. so $ P(a)=0$
therefore $ a^2,a^4,a^8$ etc. have to be roots of $ P$ also. This leeds to contradiction because we get infinitely many roots and polinomial should be of infinite degree except if $ |a|=1;0$ not hard to exclude the $ 0$ part
but if we put $ a-2$ into the expression we get $ P((a-2)^2)=P(a-2)P(a)$ meaning $ P((a-2)^2)=0$ which means again infinitely many roots with the same reason as before. except if $ |a-2|=1$
the only $ a$ such that $ |a-2|=|a|=1$ is $ a=1$ and it is the only theoretical root of the polynomial
now we put $ a_n(x-1)^n$ into starting expression and conclude that all polinomials of form $ (x-1)^n$ for any natural $ n$ are solutions plus trivial solutions $ P(x)=0$ and $ P(x)=1$
\end{solution}
\begin{solution}[by \href{https://artofproblemsolving.com/community/user/29428}{pco}]
\begin{tcolorbox}Find all $ P(x)\in R[x]$ such that
$ P(x^2) = P(x)P(x + 2)$\end{tcolorbox}
$ P(x)=0$ and $ P(x)=1$ are solution.
If $ P(x)$ is different from constant polynomial, then :
If $ z$ is a complex root, then so is $ z^2$ and so, since we have finite number of roots, all non zero roots have $ |z|=1$.
If $ 0$ is a root, $ P((-2)^2)=P(-2)P(0)$ and $ 4$ is a root, but $ |4|\neq 1$ and so $ 0$ is not a root.
If $ z$ is a complex root, then so is $ (z-2)^2$ and so all roots have $ |z|=1$ and $ |z-2|=1$
So the only complex root is $ 1$.
So $ P(x)=a(x-1)^n$ and it is easy to check that $ a=1$
So the solutions are :
$ P(x)=0$
$ P(x)=1$
$ P(x)=(x-1)^n$
\end{solution}
*******************************************************************************